Impact of Public Debt on the Economic Growth of Pakistan. (The Pakistan Development Review, 2011)
Over the years Pakistan has failed to collect enough revenues for financing of its budget. Consequently, the problem of twin deficits emerged and to finance the developmental activities government has to rely on public external and domestic debt. The positive effects of public debt relate to the fact that in resource-starved economies debt financing if done properly leads to higher growth and adds to their capacity to service and repay public debt. The negative effects work through two main channels—i.e., ―Debt Overhang‖ and ―Crowding Out‖ effects. The present study examines the consequences of public debt for economic growth and investment in Pakistan for the period 1972-2009. It develops a hybrid model that explicitly incorporates the role of public debt in growth equations. As the some variables are I (1) and other are I (0) so Autoregressive Distributed Lag(ARDL) technique has been applied to estimate the model. Study finds that public external debt has negative relationship with per capita GDP and investment confirming the existence of ―Debt Overhang effect‖. However, due to insignificant relationships of debt servicing with investment and per capita GDP, the existence of the crowding out hypothesis could not be confirmed. Similarly, domestic debt has a negative relationship with investment and per capita GDP. In other words, it seems to have crowded out private investment. JEL classification: H63, O43, E22, C22 Keywords: Public Debt, Economic Growth, Investment, ARDL